Substrate holding member

The substrate holding member with electrodes composed of W, WC, W2C, Mo, or Mo2C, and rare earth elements addresses carbonization and grain growth issues, ensuring consistent volume resistivity and temperature uniformity by stabilizing resistance values.

JP7602889B2Active Publication Date: 2024-12-19NITERRA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020175428
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-19
Publication Date
2024-12-19
Estimated Expiration
2040-10-19

AI Technical Summary

Technical Problem

Existing substrate holding members, particularly those with electrodes made of Mo or W embedded in AlN ceramics, face issues such as carbonization, grain growth, and variations in resistance values due to differences in firing conditions, leading to non-uniform temperature distribution and difficulty in maintaining consistent volume resistivity.

Method used

A substrate holding member with electrodes made of W, WC, W2C, Mo, or Mo2C, containing rare earth elements and a wire diameter of 0.02 mm to 0.15 mm, which reduces grain growth and crack formation during sintering, thereby stabilizing volume resistivity.

Benefits of technology

The solution effectively reduces variations in volume resistivity among multiple products, facilitating easier electrode design and improving temperature uniformity on the substrate mounting surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602889000001
    Figure 0007602889000001
  • Figure 0007602889000002
    Figure 0007602889000002
  • Figure 0007602889000003
    Figure 0007602889000003
Patent Text Reader

Abstract

To provide a substrate holding member capable of reducing variations in specific volume resistance of an electrode in a plurality of products manufactured under the same condition, and facilitating an electrode design.SOLUTION: A substrate holding member 100 comprises: a flat-plate like substrate holding member main body 110 having a substrate mounting surface 112 and made of a ceramic sinter body having an AIN as a main component; and an electrode 120 formed of mesh made by weaving wires, and being embedded in the substrate holding member main body 110. The electrode 120 is made of any one or more of W, WC, W2C, Mo, MoC, or Mo2C as a main component, and contains a rare earth element. A line diameter of the wire is 0.02 mm or more and 0.15 mm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a substrate holding member. [Background technology]

[0002] Conventionally, substrate holding members such as susceptors having electrodes embedded in AlN ceramics, electrostatic chucks, and ceramic heaters have been proposed as members for semiconductor manufacturing equipment.

[0003] Patent Document 1 describes a ceramic heater comprising a ceramic sintered body and a resistance heating element provided in contact with the ceramic sintered body, in which the resistance heating element contains a metal containing one or more metals selected from Groups 4a, 5a, and 6a of the periodic table and a carbide of the metal, thereby suppressing the reaction of the metal during the sintering process and suppressing fluctuations in the uniformity of the temperature on the heater heating surface. For example, Mo or W is used as the resistance heating element.

[0004] Patent Document 2 discloses a ceramic heater having a heater electrode embedded in an alumina ceramic substrate, the heater electrode being embedded in the alumina ceramic substrate and made of molybdenum containing at least a titanium component, with the main objective of improving the temperature dependency of resistivity. It is described that this ceramic heater has an improved temperature dependency of resistivity because the heater electrode is made of molybdenum containing at least a titanium component.

[0005] Patent Document 3 discloses a ceramic member in which an internal electrode and a metal lump electrically connected to the internal electrode are embedded in an AlN ceramic sintered body, with a part of the metal lump exposed to the outside. The metal lump is made of a metal obtained by adding at least one additive selected from the group consisting of potassium, oxides of rare earth elements, nitrides of rare earth elements, carbides of rare earth elements, and borides of rare earth elements to tungsten or molybdenum. It is disclosed that this makes it possible to suppress the metal lump from becoming coarse-grained and becoming embrittled due to high temperatures. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 3888531 [Patent Document 2] JP 2013-229310 A [Patent Document 3] JP 2019-9021 A Summary of the Invention [Problem to be solved by the invention]

[0007] When electrodes for heater elements, etc., made of a metal mesh whose main components are Mo and W, are embedded in a sintered body made of AlN ceramics, carbon components from the binder, jig, and environment used during firing of the AlN ceramics are mixed in and react with Mo and W, producing Mo2C, WC, and W2C, which have high volume resistivities, in some areas. Carbonization is caused by the embedded position of the electrodes in the fired body and the dimensions of the wire diameter that forms the mesh, as well as by slight differences in firing conditions, so even if multiple products are manufactured under the same conditions, not only do the electrode resistance values ​​vary between products, but it also leads to non-uniform temperature distribution in the heater within a single product, for example.

[0008] In addition, the inventors have found that when an electrode for forming a heater element or the like made of a metal mesh mainly composed of Mo or W is embedded in an AlN ceramic sintered body, the wire is likely to crack during sintering when the wire diameter is large or when the particle diameter of the wire particles is large, and this is one of the causes of the variation in resistance value between multiple products or each part of a single product. In response to this, although it was possible to suppress the occurrence of cracking during sintering to some extent by reducing the wire diameter, carbonization is likely to progress when the wire diameter is small. When carbonization progresses, the Mo and W electrode materials undergo grain growth, and as a result of the grain growth, cracking and changes in volume resistivity are likely to occur, and the volume resistivity varies, making it difficult to achieve the designed value. Therefore, an AlN ceramic heater with a stabilized volume resistivity of the heater element was desired.

[0009] However, since Patent Document 1 aims to suppress the reaction of metals during the sintering process by including a metal element and a carbide of that metal element, it is not possible to reduce the variation in resistance value or volume resistivity when carbonization is assumed to proceed. Furthermore, Patent Document 2 aims mainly to improve the inversion phenomenon of the resistivity temperature dependency, so it does not consider reducing the variation in resistance value or volume resistivity. Furthermore, Patent Document 3 aims to suppress the embrittlement of a metal lump other than the electrode, so it does not consider reducing the variation in resistance value or volume resistivity.

[0010] The inventors discovered that the occurrence of cracking can be suppressed by reducing the wire diameter, and that grain growth can be suppressed and changes in volume resistivity can be reduced by adding rare earth elements to the electrode material, and thus completed the present invention.

[0011] The present invention has been made in consideration of the above circumstances, and aims to provide a substrate holding member that can reduce variation in the volume resistivity of the electrodes in multiple products manufactured under the same conditions and that facilitates electrode design. [Means for solving the problem]

[0012] (1) In order to achieve the above object, the present invention provides a substrate holding member comprising: a flat substrate holding member body having a substrate mounting surface and made of a ceramic sintered body mainly composed of AlN; and an electrode formed of a mesh woven with wires and embedded in the substrate holding member body, the electrode containing one or more of W, WC, WC, Mo, MoC, and MoC as its main component and containing a rare earth element, and the wire has a wire diameter of 0.02 mm or more and 0.15 mm or less.

[0013] In this way, by constructing the electrodes formed of a mesh woven with the wires of the substrate holding member from a material mainly composed of any of W, WC, W2C, Mo, MoC, and Mo2C and containing rare earth elements, and by setting the wire diameter to 0.02 mm or more and 0.15 mm or less, it is possible to reduce the variation in the volume resistivity of the electrodes in multiple products manufactured under the same conditions, and it becomes easier to design the electrodes of the substrate holding member. As a result, for example, when the substrate holding member is applied to a heater, it is possible to reduce the variation in the resistance value of the electrodes between multiple products, and improve the temperature uniformity of the substrate mounting surface of each heater.

[0014] (2) In the substrate holding member of the present invention, the wire has a wire diameter of 0.10 mm or less.

[0015] In this way, by constructing the electrode from a sufficiently thin wire, the risk of the wire cracking during sintering can be further reduced, and even if the ceramic on the upper part of the electrode is constructed as a thin insulating layer, the risk of the insulating layer cracking can be further reduced.

[0016] (3) In the substrate holding member of the present invention, the electrode contains the rare earth element in an amount of 0.1 atom % or more and 3.0 atom % or less.

[0017] In this way, the effects of the present invention can be achieved even when the rare earth element concentration is low, and therefore costs can be reduced.

[0018] (4) In the substrate holding member of the present invention, the rare earth element is La or Ce.

[0019] By using such materials, it is possible to specifically configure an electrode that exhibits the effects of the present invention. Effect of the Invention

[0020] According to the present invention, it is possible to reduce the variation in the volume resistivity of the electrodes among multiple products manufactured under the same conditions, and to facilitate the design of the electrodes of the substrate holding member. As a result, for example, when the substrate holding member is applied to a heater, it is possible to reduce the variation in the resistance value of the electrodes among multiple products, and improve the temperature uniformity of the substrate mounting surface of each heater. [Brief description of the drawings]

[0021] [Figure 1] 2 is a cross-sectional view showing an example of a substrate holding member according to an embodiment. FIG. [Diagram 2] These are microscope and SEM images of a crack (crack) occurring in an electrode. [Diagram 3] 1 is a graph showing how carbonization of an electrode embedded in a substrate holding member progresses with increasing firing temperature. [Figure 4] 1 is a table showing the production conditions and measurement results of Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Next, an embodiment of the present invention will be described with reference to the drawings. In order to facilitate understanding of the description, the same reference numerals are used for the same components in each drawing, and duplicated descriptions will be omitted. In the configuration diagrams, the size of each component is conceptually shown, and does not necessarily represent the actual dimensional ratio.

[0023] [Embodiment] [Configuration of the substrate holding member] First, the configuration of the substrate holding member according to this embodiment will be described. Fig. 1 is a cross-sectional view showing an example of the substrate holding member according to this embodiment. The substrate holding member 100 according to this embodiment includes a substrate holding member body 110 and an electrode 120. The substrate holding member 100 is applied to a heater, an electrostatic chuck, etc.

[0024] The substrate holding member body 110 is made of a ceramic sintered body mainly composed of AlN (aluminum nitride), formed in a flat plate shape, and has a substrate mounting surface 112 on one of its main surfaces. A substrate is placed on the tip of the substrate holding member body. For example, the substrate mounting surface 112 may be formed as a flat surface with a plurality of protrusions protruding from the surface, and the outer shape of the substrate holding member body may be selected according to the shape of the substrate to be placed, such as a circle, a square, or the like.

[0025] The term "mainly composed of AlN" means that the ceramic sintered body contains 90 wt% or more of AlN. In order to increase the thermal conductivity, sintering aids made of oxides of 2a group elements or 3a group elements are often added to AlN ceramics. In general, the thermal conductivity increases when the amount of sintering aid added is increased, but it is known that adding more than a certain amount of sintering aid causes a decrease in thermal conductivity. However, when the content of sintering aids made of oxides of 2a group elements or 3a group elements exceeds a certain amount, the thermal conductivity decreases. Therefore, it is desirable to keep the content of sintering aids made of oxides of 2a group elements or 3a group elements to 10 volume % or less. Examples of additives of 2a group elements include Mg, Ca, Sr, Ba, etc., and examples of additives of 3a group elements include Y, La, Sm, Ce, etc.

[0026] A ceramic sintered body mainly composed of AlN has high thermal conductivity and excellent heat resistance and plasma resistance, and the thermal conductivity can be easily adjusted by adjusting the type and amount of sintering aid added. Therefore, by forming the substrate holding member body 110 from a ceramic sintered body mainly composed of AlN, it is possible to configure a substrate holding member body 110 with adjusted thermal conductivity, excellent heat resistance and plasma resistance.

[0027] The material of the electrode 120 contains at least one of W, WC, W2C, Mo, MoC, or Mo2C as a main component, and contains a rare earth element. "Containing at least one of W, WC, W2C, Mo, MoC, or Mo2C as a main component" means that the total ratio of W, WC, W2C, Mo, MoC, or Mo2C to the entire electrode 120 is 98 wt% or more. The electrode 120 preferably contains both tungsten (W) and tungsten carbide (WC or W2C), or both molybdenum (Mo) and molybdenum carbide (MoC or Mo2C).

[0028] The rare earth element contained in the electrode 120 may be La, Ce, Nd, Dy, Er, or the like. Of these, the rare earth element is preferably La or Ce. The rare earth element contained in the electrode 120 is effective even if its concentration is small. Therefore, the rare earth element contained in the electrode 120 is preferably 0.1 atom % or more and 3.0 atom % or less. This allows costs to be reduced. The rare earth element may be added as a metal, or may be added in the form of an oxide, carbide, or nitride. These metals are produced by conventional metallurgical techniques.

[0029] The recrystallization temperature of Mo or W increases when rare earth elements are contained in Mo or W. The inventors have found that when rare earth elements are contained in Mo or W constituting an electrode, even if an electrode embedded in an AlN ceramic is fired at a high temperature together with the AlN ceramic, the grain growth of the particles constituting the electrode is suppressed, and the particles constituting the electrode do not become coarse grained. Since rare earth elements exist in the grain boundaries of Mo or W, it is presumed that they have an effect of suppressing grain growth of Mo or W. It is also known that even if a small amount of rare earth elements are added to Mo or W, they do not affect the properties of Mo or W very much. As a result, it has been found that even if the particles constituting the electrode are carbonized and embrittled, the risk of cracks (cracks) occurring in the electrode and the risk of changes in volume resistivity occurring are reduced, and the variation in resistance value is reduced. FIG. 2 shows a microscope image and an SEM image when a crack (crack) occurs in the electrode. When such a crack occurs in the electrode, the resistance at that part may be high.

[0030] The wire forming the mesh of the electrode 120 has a wire diameter of 0.02 mm or more and 0.15 mm or less. W and Mo have high melting points and are difficult to process, so wires with a wire diameter of less than 0.02 mm are difficult to manufacture. In addition, if a mesh is formed by weaving wires with a wire diameter of more than 0.15 mm, there is a high risk of the wire cracking during sintering. In addition, the thickness of the mesh at the intersection of the wires becomes larger than 0.3 mm, and when the ceramics on the upper part of the electrode 120 are configured as a thin insulating layer, there is an increased risk of cracking the insulating layer. Therefore, it is preferable that the wire has a wire diameter of 0.10 mm or less. In this way, by configuring the electrode 120 with sufficiently thin wires, it is possible to further reduce the risk of the wire cracking during sintering, and even if the ceramics on the upper part of the electrode 120 are configured as a thin insulating layer, it is possible to further reduce the risk of cracking the insulating layer.

[0031] The substrate holding member body 110 may include a plurality of electrodes. For example, by including a heater electrode and an electrostatic attraction electrode, the substrate holding member 100 can be used as an electrostatic chuck with a heater. In that case, at least one of the electrodes may be the electrode 120 of the present invention. Two or more electrodes may be the electrode 120 of the present invention. The substrate holding member 100 in FIG. 1 shows an example in which the electrode 120 on the substrate mounting surface 112 side is an electrostatic attraction electrode, and the electrode 120 on the opposite side is a heater electrode.

[0032] The substrate holding member 100 is provided with necessary terminals and terminal holes in addition to those described above, which allow power to be supplied to the electrodes 120. The terminals and terminal holes are not shown in FIG.

[0033] The substrate holding member of the present invention can reduce the variation in the volume resistivity of the electrodes among multiple products manufactured under the same conditions, making it easier to design the electrodes of the substrate holding member. As a result, for example, when the substrate holding member is applied to a heater, the variation in the resistance value of the electrodes among multiple products can be reduced, and the temperature uniformity of the substrate mounting surface of each heater can be improved.

[0034] [Method of manufacturing the substrate holding member] Next, a method for manufacturing the substrate holding member according to this embodiment will be described. The substrate holding member according to this embodiment is manufactured, for example, by a powder hot pressing method. The powder hot pressing method is a method in which ceramic raw material powder and a predetermined electrode are alternately stacked to embed the electrodes inside the ceramic, and then uniaxial hot pressing and firing is performed. By employing the powder hot pressing method, the substrate can be manufactured in a short period of time. Note that the manufacturing method is not limited to this method, and may be, for example, a molded body hot pressing method disclosed in Japanese Patent No. 6148845, a conventional green sheet lamination method, or the like.

[0035] For example, additives such as sintering aids, binders, plasticizers, and dispersants are appropriately added to and mixed with AlN ceramic powder to prepare ceramic raw material powder (slurry), and the raw material powder (granules) is granulated by a spray-drying method, etc. The mixing method may be either wet or dry, and a mixer such as a ball mill or a vibration mill may be used.

[0036] The AlN ceramic powder is preferably of high purity, preferably 96% or more, more preferably 98% or more, and has an average particle size of preferably 0.1 μm to 1.0 μm, more preferably 0.3 μm to 0.8 μm.

[0037] Since the sintering temperature of AlN ceramics is high, the material of the electrodes embedded in the sintered AlN ceramics must be a high melting point metal. For this reason, Mo or W containing rare earth elements is used for the electrode material. These electrodes are embedded when the AlN ceramics is formed and sintered at the same time. The wires that form the electrode mesh have a wire diameter of 0.02 mm to 0.15 mm. Parts of the electrodes are carbonized during sintering, but there is almost no change in wire diameter before and after sintering.

[0038] Sintering is preferably performed by uniaxial hot press firing. A bottomed carbon mold is filled with raw material powder that corresponds to the insulating layer of the electrostatic chuck, and an electrode cut into a specified shape after uniaxial pressing is placed on the compact. The same raw material powder is filled on top of it, and a carbon punch is placed on it to form it, and then hot press firing is performed at a temperature of 1700°C to 2000°C and a pressure of 1 MPa to 20 MPa for 0.1 to 20 hours. After firing, the substrate mounting surface and back surface are processed into the specified shape.

[0039] Necessary terminal holes are provided in the fired substrate holding member body 110. Then, terminals are connected to the terminal holes with brazing material or the like. The terminals may be made of Ni or the like. The brazing material may be Au brazing material or the like.

[0040] In this way, it is possible to reduce the variation in the volume resistivity of the electrodes among a plurality of products manufactured under the same conditions, and it is possible to manufacture a substrate holding member with easy electrode design.

[0041] [Examples and Comparative Examples] (Electrode carbonization experiment) FIG. 3 is a graph showing how the carbonization of an electrode embedded in a substrate holding member progresses with increasing sintering temperature. A plurality of samples were prepared in which a mesh electrode using the same 1 atom % La-added Mo wire as in Example 1 was embedded in a ceramic molded body using granules of ceramic raw material powder mainly composed of AlN as in the examples and comparative examples. Each graph in FIG. 3 shows the intensity of diffracted X-rays in XRD of the electrodes after sintering for these samples at sintering temperatures of 800°C, 1000°C, 1200°C, 1400°C, and 1800°C, the same as in the examples.

[0042] The bottom graph shows the diffracted X-rays of the electrode before firing. The two graphs above show the diffracted X-rays of the central electrode and the peripheral electrode of the sample fired at 800°C. The graphs below show the central and peripheral parts of the sample fired at 1000°C, followed by graphs at 1200°C and 1400°C. The top two graphs are for the sample fired at 1800°C, the same as in the example. The central electrode refers to the electrode closest to the center in a cross section passing through the center of the sample. The peripheral electrode refers to the electrode closest to 0.9R from the center, when the total length of the same cross section passing through the center of the sample is 2R.

[0043] As shown in the graph of FIG. 3, a peak indicating Mo was detected at around 40.7° in the unfired sample or the sample fired at 800°C. As the firing temperature increased to 1000°C and 1200°C, a peak indicating Mo2C was detected at around 39.6°, and the peak indicating Mo became smaller. In the sample fired at 1800°C, peaks of Mo and Mo2C were detected in the electrode near the center, and a peak of Mo2C was detected in the electrode at the outer periphery. In addition, although not shown, in the conventional electrode to which no rare earth elements were added, peaks of Mo and Mo2C were detected in the center when fired at 1800°C, and a peak of Mo2C was detected in the outer periphery.

[0044] This experiment showed that even electrodes containing rare earth elements did not affect carbonization.

[0045] Example 1 Ceramic raw powder, mainly composed of AlN with 5wt% Y2O3 added, was prepared. Additives such as binder, plasticizer, and dispersant were appropriately added and mixed to prepare a slurry of ceramic raw powder, which was then granulated by spray drying. Raw powder (granules) corresponding to the insulating layer of the substrate holding member was filled into a bottomed carbon mold, and after uniaxial pressing, an electrode was placed on the compact. The same raw powder was filled on top of it, a carbon punch was placed on it, and hot press sintering was performed under pressure and temperature conditions of 1800°C and 10MPa. After sintering, the substrate mounting surface and back surface were formed, and the substrate was machined to the specified shape (diameter 300mm, thickness 20mm), and holes were drilled on the back surface to expose the seat of the electrode for resistance measurement.

[0046] The electrodes were embedded with cut pieces of Mo mesh (mesh size #50). The wire diameter Φ of the Mo mesh was 0.05 mm, and the wire composition was Mo with 1 atom% La added. The electrode shape was a pattern with a constant width (5 mm) and both ends, and a seat for measuring resistance was provided at both ends of the electrode. Three identical electrostatic chucks were produced under the same conditions.

[0047] (Evaluation method) The resistance values ​​of the electrodes that were not embedded in the ceramic sintered compact before firing, and the electrodes after firing, were measured with a tester, and the rate of change and the variation in the rate of change were evaluated. The resistance values ​​before and after firing are the average values ​​of multiple samples made under the same conditions. The variation in resistance values ​​was evaluated as (maximum resistance - minimum resistance) / average resistance value for multiple samples made under the same conditions. The particle size of the electrode was evaluated by cutting the test piece after resistance evaluation and observing the wire cross section with a SEM at 2000x magnification. The composition of the electrode was determined using an X-ray diffraction device and EPMA.

[0048] The evaluation results of Example 1 were that the average resistance value before firing was 0.120Ω, the average resistance value after firing was 0.257Ω, the rate of change in resistance was 114%, the variation was 8.2%, the particle size of the electrode before firing was 20μm, the particle size of the electrode after firing was 34μm in the center and 37μm in the outer periphery, the composition of the electrode after firing was Mo, Mo2C in the center and Mo2C in the outer periphery, and the structure of the electrode after firing was crack-free in both the center and outer periphery. The positions of the center and outer periphery were the same as above.

[0049] Example 2 Example 2 was produced under the same conditions as Example 1, except that the wire diameter Φ was set to 0.10 mm. The evaluation results showed that the average resistance value before firing was 0.080Ω, the average resistance value after firing was 0.129Ω, the resistance change rate was 61.3%, the variation was 5.4%, the particle size of the electrode before firing was 20 μm, the particle size of the electrode after firing was 32 μm in the center and 35 μm in the outer periphery, the composition of the electrode after firing was Mo, Mo2C in the center and Mo2C in the outer periphery, and the structure of the electrode after firing was crack-free in both the center and outer periphery.

[0050] Example 3 Example 3 was produced under the same conditions as Example 1, except that the wire diameter was Φ0.15 mm. The evaluation results showed that the average resistance value before firing was 0.065Ω, the average resistance value after firing was 0.097Ω, the resistance change rate was 49.7%, the variation was 4.8%, the particle size of the electrode before firing was 20μm, the particle size of the electrode after firing was 30μm in the center and 33μm in the outer periphery, the composition of the electrode after firing was Mo, Mo2C in the center and Mo, Mo2C in the outer periphery, and the structure of the electrode after firing was crack-free in both the center and outer periphery.

[0051] Example 4 Example 4 was produced under the same conditions as Example 2, except that the wire composition was Mo with 0.1 atom % La added. The evaluation results showed that the average resistance value before firing was 0.076 Ω, the average resistance value after firing was 0.130 Ω, the resistance change rate was 71.0%, the variation was 6.4%, the particle size of the electrode before firing was 22 μm, the particle size of the electrode after firing was 42 μm in the center and 45 μm in the outer periphery, the composition of the electrode after firing was Mo, Mo2C in the center and Mo2C in the outer periphery, and the structure of the electrode after firing was crack-free in both the center and outer periphery.

[0052] Example 5 Example 5 was produced under the same conditions as Example 2, except that the wire composition was Mo with 3 atom% La added. The evaluation results were that the average resistance value before firing was 0.097Ω, the average resistance value after firing was 0.175Ω, the resistance change rate was 80.4%, the variation was 5.0%, the particle size of the electrode before firing was 26 μm, the particle size of the electrode after firing was 37 μm in the center and 41 μm in the outer periphery, the composition of the electrode after firing was Mo, Mo2C in the center and Mo2C in the outer periphery, and the structure of the electrode after firing was crack-free in both the center and outer periphery.

[0053] Example 6 Example 6 was produced under the same conditions as Example 2, except that the wire composition was Mo with 1 atom% Ce added. The evaluation results showed that the average resistance value before firing was 0.083Ω, the average resistance value after firing was 0.145Ω, the resistance change rate was 74.7%, the variation was 5.1%, the particle size of the electrode before firing was 25μm, the particle size of the electrode after firing was 35μm in the center and 40μm in the outer periphery, the composition of the electrode after firing was Mo, Mo2C in the center and Mo2C in the outer periphery, and the structure of the electrode after firing was crack-free in both the center and outer periphery.

[0054] Example 7 Example 7 was produced under the same conditions as Example 2, except that the wire composition was W with 1 atom % La added. The evaluation results were that the average resistance value before firing was 0.055Ω, the average resistance value after firing was 0.091Ω, the resistance change rate was 65.5%, the variation was 4.9%, the particle size of the electrode before firing was 22 μm, the particle size of the electrode after firing was 27 μm in the center and 35 μm in the outer periphery, the electrode composition after firing was W, WC, W2C in the center and W, WC, W2C in the outer periphery, and the structure of the electrode after firing was crack-free in both the center and outer periphery.

[0055] Comparative Example 1 Comparative Example 1 was produced under the same conditions as Example 1, except that the wire composition was only Mo. The evaluation results were that the average resistance value before firing was 0.124Ω, the average resistance value after firing was 0.469Ω, the resistance change rate was 278%, the variation was 14.4%, the particle size of the electrode before firing was 27μm, the particle size of the electrode after firing was 70μm in the center and 75μm in the outer periphery, the electrode composition after firing was Mo, Mo2C in the center and Mo2C in the outer periphery, and the structure of the electrode after firing was no cracks in the center and cracks occurred in the outer periphery.

[0056] Comparative Example 2 Comparative Example 1 was produced under the same conditions as Example 2, except that the wire composition was only Mo. The evaluation results were that the average resistance value before firing was 0.090Ω, the average resistance value after firing was 0.284Ω, the rate of change in resistance was 216%, the variation was 10.6%, the particle size of the electrode before firing was 27μm, the particle size of the electrode after firing was 70μm in the center and 72μm in the outer periphery, the composition of the electrode after firing was Mo, Mo2C in the center and Mo2C in the outer periphery, and the structure of the electrode after firing was no cracks in the center and cracks occurred in the outer periphery.

[0057] The table in FIG. 4 shows the manufacturing conditions and evaluation results of the examples and comparative examples. In Example 1, the particle size of Mo constituting the electrode is kept small even when it is converted to Mo2C, so it is presumed that the toughness is kept relatively high. In addition, the wire diameter is not too large, and the stress during hot pressing, i.e., the stress in the tensile direction, is influenced by (hot pressing pressure / wire diameter) and suppressed, so it is presumed that no cracks were generated in the electrode. As a result, it is presumed that the variation in resistance was relatively suppressed even if the composition of the electrode differed between the center and the outer periphery.

[0058] In Example 2, even though a portion of the electrode was converted to Mo2C as in Example 1, the particle size was kept small by adding La, and in addition, the toughness was improved, and the wire diameter was larger than in Example 1, so the stress (stress in the direction of compression) during hot pressing was further suppressed, and therefore it is presumed that no cracks occurred in the electrode. As a result, it is presumed that the relative variation in resistance was kept small even though the composition of the electrode differed between the center and outer periphery.

[0059] Example 3 is an example in which the wire diameter is further increased compared to Examples 1 and 2. Because the wire diameter was increased, even in the outer periphery, Mo did not all become Mo2C by sintering, but became a mixed crystal structure of Mo and Mo2C. As a result, it is presumed that the rate of change in resistance was relatively small because there was little formation of Mo2C, which shows relatively high resistance. At the same time, it is presumed that no cracks occurred because relatively ductile Mo remained even though the wire diameter was increased.

[0060] In Example 4, even though the amount of added rare earth elements was small, some of the particles were converted to Mo2C as in Example 2, and the particle size was kept small, and the toughness was improved, which is presumably why no cracks occurred in the electrode. As a result, it is presumed that the relative variation in resistance was kept small even though the composition of the electrode differed between the center and outer periphery.

[0061] In Example 5, even though the amount of added rare earth elements was relatively large, some of the particles were converted to Mo2C and the particle size was kept small, as in Example 2, and there was also an effect of improving toughness, which is presumably why no cracks occurred in the electrode. As a result, it is presumed that the relative variation in resistance was kept small even though the composition of the electrode differed between the center and outer periphery.

[0062] In Example 6, a different rare earth element was added, but the same effect was obtained as in Example 2. This is presumably because the ionic radii of the rare earth elements were relatively similar, and therefore the effect was obtained regardless of the type of rare earth element.

[0063] In Example 7, the main component of the electrode material is W. Both Mo and W belong to Group 6A of the periodic table and have similar properties. Therefore, it is presumed that the addition of rare earth elements also has a similar effect.

[0064] In Comparative Example 1, it is presumed that the wire with a wire diameter of Φ0.05 mm was embrittled as a whole due to the generation of Mo2C in the outer periphery, and the toughness was reduced due to grain growth, causing the wire to crack. As a result, it is presumed that the resistance of the outer periphery was high and the variation was large.

[0065] In Comparative Example 2, although some Mo remains in the electrode structure, it is presumed that the wire diameter is large and cracks (cracks) have occurred in the electrode due to the pressure during hot pressing.

[0066] From the above, it has been confirmed that the substrate holding member of the present invention is capable of reducing the variation in the volume resistivity of the electrodes in multiple products manufactured under the same conditions, and is a substrate holding member that facilitates electrode design.

[0067] The present invention is not limited to the above-described embodiment, and it goes without saying that various modifications and equivalents are included within the spirit and scope of the present invention. In addition, the structure, shape, number, position, size, etc. of the components shown in each drawing are for convenience of explanation and may be changed as appropriate. [Explanation of symbols]

[0068] 100 Substrate holding member 110 Substrate holding member body 112 Substrate mounting surface 120 electrodes

Claims

1. A substrate holding member, a flat-plate-shaped substrate holding member body having a substrate mounting surface and made of a ceramic sintered body mainly composed of AlN; an electrode formed of a mesh woven with wires and embedded in the substrate holding member body; The electrodes are made of W, WC, or W. 2 C, Mo, MoC, or Mo 2 C as a main component and containing a rare earth element; The wire has a diameter of 0.02 mm or more and 0.15 mm or less.

2. 2. The substrate holding member according to claim 1, wherein the wire has a diameter of 0.10 mm or less.

3. 3. The substrate holding member according to claim 1, wherein the electrode contains the rare earth element in an amount of 0.1 atom % or more and 3.0 atom % or less.

4. 4. The substrate holder according to claim 1, wherein the rare earth element is La or Ce.

Citation Information

Patent Citations

  • Bonding agent for base material of aluminum nitride-based ceramic

    JP2004345952A

  • Aluminum nitride sintered compact

    JP2007186382A

  • Low-thermal-expansion ceramic member, and manufacturing method thereof

    JP2008124265A

  • Ceramic heater, heater electrode, and method of manufacturing ceramic heater

    JP2013229310A

  • Ceramic member and manufacturing method of the same

    JP2019009021A